Porphyrin‐Based COF 2D Materials: Variable Modification of Sensing Performances by Post‐Metallization. Issue 12 (31st January 2022) - Liu, Ming; Chen, Yong‐Jun; Huang, Xin; Dong, Long‐Zhang; Lu, Meng; Guo, Can; Yuan, Daqiang; Chen, Yifa; Xu, Gang; Li, Shun‐Li; Lan, Ya‐Qian
Abstract: 2D nanomaterials with flexibly modifiable surfaces are highly sought after for various applications, especially in room‐temperature chemiresistive gas sensing. Here, we have prepared a series of COF 2D nanomaterials (porphyrin‐based COF nanosheets (NS)) that enabled highly sensitive and specific‐sensing of NO2 at room temperature. Different from the traditional 2D sensing materials, H2 ‐TPCOF was designed with a largely reduced interlayer interaction and predesigned porphyrin rings as modifiable sites on its surfaces for post‐metallization. After post‐metallization, the metallized M‐TPCOF (M=Co and Cu) showed remarkably improved sensing performances. Among them, Co‐TPCOF exhibited highly specific sensing toward NO2 with one of the highest sensitivities of all reported 2D materials and COF materials, with an ultra‐low limit‐of‐detection of 6.8 ppb and fast response/recovery. This work might shed light on designing and preparing a new type of surface‐highly‐modifiable 2D material for various chemistry applications. Abstract : A series of metalloporphyrin covalent organic framework based nanosheets has been synthesized and successfully applied in specific sensing of NO2 at room temperature.